(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the efficacy & safety of magnesium sulphate in 12 hours regime versus 24 hours regime after last fit in eclamptic patients. Study Design: Randomized controlled trial study Place and Duration of Study: This randomized controlled trial was carried out at Department of Obstetrics and Gynaecology, Unit-III, Nishtar Medical College/Hospital Multan from 01.06.2013 to 31.05.2014. Materials and Methods: Total 120 patients with eclampsia were included. All patients were given 4g of magnesium sulphate (20% solution) intravenously slowly (15 mins) as loading dose. After receiving the loading dose randomization was performed by block design. So 60 patients for 12 hour regime while 60 patients for 24 hour regime (control group). In 12 hour regime group magnesium sulphate maintenance dose of 1g (20% solution) was given 1 hourly intravenously for 12 hours after last fit. In 24 hour regime group magnesium sulphate maintenance dose of 1g (20% solution) was given 1 hourly intravenously for 24 hours after last fit. Efficacy in shape of recurrence of fits, number of fits and safety in shape of pulmonary oedema, oliguria and loss of knee jerk reflex, Nausea and flushing was noted. Results: Total 120 patients were studied falling in age group of 20 to 40 years. Eclampsia was most commonly occurring in young and primigravida patients. Majority of eclamptic patient had diastolic B.P 110 or > 110mmHg. None of patients in either group had eclamptic fit. Loss of knee jerk reflex seen in 5 patients in 24hrs regime group. Minor side effects were more commonly observed in 24hrs regime group. (n=38) of the students were underweight and 36 %( n=21) were obese. Conclusion: Twelve hours regime is equally effective as 24hours regime but with lesser side effects & so more cost effective. 12hours regime was observed to promote shorter hospital stay decreasing work load.